Pengaruh Influencer Marketing dan Brand Image terhadap Keputusan Pembelian Tepung Tapioka di Kota Surabaya - Thomas Yoito Ady Gawi; Fransisia C S Rani; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to analyze the influence of influencer marketing and brand image on tapioca flour purchasing decisions in Surabaya. The research approach used is quantitative, with a sample of 100 respondents through the distribution of questionnaires boldly using Google Form. The sample was selected using convenience sampling techniques, with respondents who were consumers of tapioca flour. The data collected included primary and secondary data. Data analysis was carried out using the Partial Least Square (PLS) method, and involved validity, reliability, and hypothesis testing. The results showed that influencer marketing and brand image had a positive and significant influence on tapioca flour purchasing decisions in the city of Surabaya.